DETEKSI DETERMINAN KINERJA KARYAWAN - Endah Yunianti; Sri Yuni Widowati; Aprih Santoso (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
This study was motivated by the decline in targets at PT. Mod Indi Semarang. For this reason, the problem can be formulated is how the sewing part efforts improve Employee Performance so that production is achieved. The purpose of this study was to analyze the influence of the Work Environment, Leadership, and Motivation on Employee Performance in the part of sewing production at PT. Indo Mod Semarang. The population of this study was 420 production employees at sewing PT. Indo Mod Semarang. The sample used in this study was 81 respondents using purposive sampling technique, which is a sampling technique that provides an opportunity to become a member of the sample with certain criteria. Then the method of collecting data through questionnaires and data analysis using SPSS 22 which includes tests of validity, reliability, classic assumption tests, multiple regression analysis, hypothesis testing using a t-test, F test, R2 test. The results of this study indicate that all independent variables, namely Work Environment, Leadership, and Motivation have a positive and significant effect on employee performance. Based on the determination coefficient value of 0.884, it is known that in this study the Work Environment, Leadership, and Motivation has a consequent on the variable employee performance of 88.4% while the rest, which is 11.6% is influenced by other variables that are not explained.